High prevalence of urogenital infection/inflammation in patients with azoospermia does not impede surgical sperm retrieval. (27th August 2019) - Pilatz, Adrian; Kilb, Jill; Kaplan, Huelya; Fietz, Daniela; Hossain, Hamid; Schüttler, Christian G.; Diemer, Thorsten; Bergmann, Martin; Domann, Eugen; Weidner, Wolfgang; Wagenlehner, Florian; Schuppe, Hans-Christian
Abstract: Considering infection/inflammation to be an important risk factor in male infertility, the aim of this study was to make a comprehensive evaluation of the prevalence of urogenital tract infection/inflammation and its potential impact on sperm retrieval in azoospermic patients. In this prospective study, 71 patients with azoospermia were subjected to an extensive andrological workup including comprehensive microbiological diagnostics (2‐glass test, semen, testicular swab and testicular tissue analysis) and testicular biopsy/testicular sperm extraction (TESE). Medical history suggested urogenital tract infection/inflammation in 7% of patients, 11% harboured STIs, 14% showed significant bacteriospermia, 15% had seminal inflammation, 17% fulfilled the MAGI definition, and 27% had relevant pathogens. At the testicular level, 1 patient had a swab positive for bacteria, no viruses were detected, tissue specimens never indicated pathogens, whereas histopathology revealed focal immune cell infiltrates in 23% of samples. Testicular sperm retrieval rate was 100% in obstructive and 46% in nonobstructive azoospermia. None of the infection/inflammation‐related variables was associated with the success of sperm retrieval or inflammatory lesions in the testis. The high prevalence of urogenital infection/inflammation among azoospermic men underpins their role as significant aetiologic factors in male infertility. However, this observation does not refer to the chances of sperm retrieval at the time of surgery/TESE.